Educational Financing Systems in Islamic Junior Secondary Schools: A Case Study - Muchamad Wahyu Jum’adi; Wahidmurni (Journal of Educational Management Research, 2026)
This study aims to analyze educational financing systems to improve the quality of education, focusing on three main aspects: planning, implementation, and financial accountability. A qualitative case study approach was employed, with data collected through observations, interviews, and documentation. The participants included school leaders and administrative staff responsible for financial management. The findings reveal that educational financing is systematically planned by identifying priority programs and determining student-related costs, followed by the preparation of an annual school budget plan based on students’ needs. In the implementation stage, government funding is primarily allocated to support national education standards, while additional funding sources, such as community contributions and donations, are used to address unmet needs. Financial accountability is maintained through annual financial reports detailing income and expenditures. The study implies that effective educational financing management requires structured planning, diversified funding sources, and transparent accountability practices. These elements are essential for ensuring financial sustainability and improving educational quality, particularly within the framework of educational management.